Implementasi proyek penguatan profil pelajar pancasila (P5) di sekolah dasar - Pravitasari, Pinkan Dwi; Mahfud, Hasan; Supianto, Supianto (Universitas Sebelas Maret, 2023)
This research aims to determine the implementation of the project to strengthen the Pancasila student profile (P5) in Elementary school. This research method uses qualitative research. Primary data from this study were the results of interviews with class I and IV subject teachers and students. While secondary data is in the form of research photo documentation, project implementation photo documentation, and project modules. Data collection techniques used are interviews and documentation. Test the validity of the data using technique and source triangulation. The data analysis technique used is the Miles and Huberman technique. The results of this study indicate that the implementation of the Pancasila student profile strengthening project (P5) is to the guidelines. However, several components have not been implemented / attitude of learners. Barriers to students are mood swings, disruptive behavior in class, making dummy pancakes, and lack of self-motivation in learning. The solution to teacher barriers is to cooperate with IOM and teacher fees, carry out extra supervision, form team groups, and maintain emotional self-esteem. The student's solution is to ask for help from the project teacher and accompanying parents and to distribute tasks evenly within the group.